Taxonomic novelties in Southern Brazilian Amaryllidaceae – IV: Hippeastrum correiense (Bury) Worsley, the correct name of the famous H. morelianum Lem.; and H. verdianum, a new species from Santa Catarina. - Büneker, Henrique Mallmann; Bastian, Regis Eduardo (Balduinia, 2018)
In this article, Hippeastrum verdianum, a new species of Amaryllidaceae (Amaryllidoideae, Hippeastreae), which occurs in rocky cliffs in Santa Catarina (Brazil), is described and illustrated. Data are provided on their habitat, ecology and geographical distribution. The new species shows morphological affinity with H. correiense and H. papilio. In order to establish a consistent argumentative basis for the description of the new species, we clarify the taxonomic identity of H. correiense, proposing lectotypes for it as well as other binomials that we consider as synonyms.